Implementation project of the non-pneumatic anti-shock garment and m-communication to enhance maternal health care in rural Tanzania - Godfrey Mbaruku; Michelle Skaer Therrien; Robert Tillya; Selemani Mbuyita; Zacharia Mtema; Iddajovana Kinyonge; Ritha Godfrey; Silas Temu; Suellen Miller (BMC, 2018)
Abstract Background Obstetric hemorrhage (OH) remains one of the leading causes of maternal mortality, particularly in rural Africa. Tanzania has a high maternal mortality ratio, and approximately 80% of the population accesses health care lower level facilities, unable to provide Comprehensive Emergency Obstetric Care (CEmOC). The non-pneumatic anti-shock garment (NASG) has been demonstrated to reduce mortality as it buys time for women in shock to be transported to or to overcome delays at referral facilities. Methods This report describes one component of an ongoing maternal health improvement project, Empower, implemented in 280 facilities in four regions in rural Tanzania. The NASG along with a Closed User Group (CUG) mobile phone network were implemented within the overall EmOC project. Simulation trainings, repeated trainings, and close hands-on supportive supervision via site visits and via the CUG network were the training/learning methods. Data collection was conducted via the CUG network, with a limited data collection form, which also included free text options for project improvement. One-to-one interviews were also conducted. Outcome Indicators included appropriate use of NASG for women with hypovolemic shock We also compared baseline case fatality rates (CFR) from OH with endline CFRs. Data were analyzed using cohort study Risk Ratio (RR). Qualitative data analysis was conducted by content analysis. Results Of the 1713 women with OH, 419 (24.5%) met project hypovolemic shock criteria, the NASG was applied to 70.8% (n = 297), indicating high acceptability and utilization. CFR at baseline (1.70) compared to CFR at endline (0.76) showed a temporal association of a 67% reduced risk for women during the project period (RR: 0.33, 95% CI = .19, .60). Qualitative feedback was used to make course corrections during the project to enhance training and implementation. Conclusions This implementation project with 280 facilities and over 1000 providers supported via CUG demonstrated that NASG can have high uptake and appropriate use for hypovolemic shock secondary to OH. With the proper implementation strategies, NASG utilization can be high and should be associated with decreased mortality among mothers at risk of death from obstetric hemorrhage.